Sevoflurane Alleviates Myocardial Ischemia Reperfusion Injury by Inhibiting P2X7-NLRP3 Mediated Pyroptosis - Wu, Jiaxuan; Cai, Wenfeng; Du, Ruiming; Li, Haiyang; Wang, Bin; Zhou, Yanqiong; Shen, Daifei; Shen, Huimin; Lan, Yang; Chen, Lesi; Zheng, Xiaoxia; Huang, Danmei; et al. (Frontiers in Molecular Biosciences, 2021)
Myocardial ischemia is common in aging population. This study investigates the protective effect of Sevoflurane on myocardial ischemia reperfusion injury (MIRI) and its underlying mechanism. A total of 87 patients with a history of myocardial ischemia who underwent abdominal surgery with Sevoflurane general anesthesia were recruited in the study. The clinical data, blood pressure, heart rate, pressure-rate quotient (PRQ) and rate-pressure product (RPP) were recorded. Serum samples were collected and heart-type fatty acid binding protein (H-FABP), ischemia modified albumin (IMA), interleukin-1β (IL-1β), and interleukin-18 (IL-18) were measured to observe whether Sevoflurane anesthesia had protective effect on myocardium. In addition, MIRI rats and hypoxia/reoxygenation(H/R) injury cell model was established using neonatal rat ventricular myocytes (NRVM). Rats or NRVM were pretreated with sevoflurane for 45min before hypoxia. The mRNA expression of purinergic receptor-7 (P2X7) and NLR family pyrin domain containing 3(NLRP3) were examined. The protein expression of P2X7, NLRP3, apoptosis-associated speck-like protein (ASC), cysteine aspartic acid specific protease-1(Caspase-1), Gasdermin-D (GSDMD), Bcl-2 Associated X Protein (Bax), B-cell lymphoma-2 (Bcl-2) in myocardial tissue and cells were evaluated. The serum contents of IL-1β, IL-18, Malondialdehyde (MDA), Superoxide Dismutase (SOD), Lactate Dehydrogenase (LDH), Creatine kinase (CK), and Creatine kinase isoenzymes (CK-MB) were measured. The cellular localization and fluorescence intensity of NLRP3 and ASC in cells were detected. It was found that the secretion of IL-1β and IL-18 decreased in the patients. After I45min/R3h in SD rats and H3h/R1h in NRVM, the protein expressions of P2X7, NLRP3, ASC, Caspase-1 and GSDMD were increased, the release of IL-1β, IL-18, CK, CK-MB, LDH and MDA were increased, and SOD activity was decreased. Sevoflurane treatment inhibited the high expression of P2X7, NLRP3, ASC, Caspase-1 and GSDMD, inhibited the release of LDH, CK,CK-MB and MDA in cells, and improved the activity of SOD, indicating that Sevoflurane alleviated the damage of MIRI of rats and H/R of NRVM, and had myocardial protective effect. Taken together, our study suggests that Sevoflurane inhibited the expression of IL-1β, IL-18 and GSDMD by inhibiting the P2X7-NLRP3 signaling pathway. It reduced the H/R injury of cardiomyocytes and protected the cardiac function by regulating inflammatory reaction and pyroptosis